On the potential of using peculiarities of the protein intrinsic disorder distribution in mitochondrial cytochrome b to identify the source of animal meats. (1st January 2017) - Yacoub, Haitham A.; Sadek, Mahmoud A.; Uversky, Vladimir N.
ABSTRACT: This study was conducted to identify the source of animal meat based on the peculiarities of protein intrinsic disorder distribution in mitochondrial cytochrome b (mtCyt- b ). The analysis revealed that animal and avian species can be discriminated based on the proportions of the two groups of residues, Leu+Ile, and Ser+Pro+Ala, in the amino acid sequences of their mtCyt- b . Although levels of the overall intrinsic disorder in mtCyt- b is not very high, the peculiarities of disorder distribution within the sequences of mtCyt- b from different species varies in a rather specific way. In fact, positions and intensities of disorder/flexibility "signals" in the corresponding disorder profiles are relatively unique for avian and animal species. Therefore, it is possible to devise a set of simple rules based on the peculiarities of disorder profiles of their mtCyt- b proteins to discriminate among species. This intrinsic disorder-based analysis represents a new technique that could be used to provide a promising solution for identification of the source of meats.